EDUCATIONAL ROBOTS IN TEACHERS’ EDUCATION - Danimir Mandić; Gordana Miščević; Jelica Babić; Sofija Matović (Istraživanja u Pedagogiji)
The contemporary educational paradigm, which brings learning outcomes and competencies to the foreground, puts special emphasis on digital competencies. The relevance of their development is visible in a series of strategies and initiatives at the global and national level. The application of AI and robotics poses a number of pedagogical challenges to teachers, with the use of robots in education being one of the latest trends. The paper discusses the perceptions of students of the University of Belgrade’s Faculty of Education (Serbia) about robots. The aim of the research was to determine how future preschool and primary school teachers perceive robots, and their pedagogical implications, in order to create opportunities for improving teaching on the use of robots in an educational setting. Students perceive robots in two dominant functions: educational and assistive. A statistically significant difference in the attitudes of future preschool and primary school teachers were observed regarding the reasons for choosing the robot they drew. Preschool teachers gave primacy to the cognitive domain, while primary school teachers found it difficult to judge which domain was dominant. Misconceptions about robots were observed among some of the respondents, and these were further analyzed. The most dominant function of the robot was the educational one, and its predominant appearance was in the animal form. Most of the respondents did not draw elements that would indicate emotions of the depicted robots. However, the drawings of the robot in the animal form included clear positive emotions. The obtained results can be a significant predictor of the way in which future preschool and primary school teachers will use robots in their teaching and educational work with children and students. They can also give the professors of the faculties of education useful guidelines for modifying syllabuses used for building student digital competencies.